Olefin polymer and preparation method thereof
Through the slurry polymerization process and the rigid skeleton bridged lenocene-fluorene metal compound catalyst, a long branched polyethylene powder was prepared, which solved the problems of long swelling time and poor processing performance of high molecular weight polyethylene powder, and achieved efficient swelling and improve processing performance, suitable for lithium battery separators and other applications.
Patent Information
- Application Number
- CN202310921294.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-25
- Publication Date
- 2024-12-13
AI Technical Summary
The high molecular weight polyethylene powder swells in the solvent for a long time, has poor processing performance, and the cost increases and the mechanical properties decrease after the introduction of the branched chain structure, making it difficult to improve production efficiency and product performance.
The long branched polyethylene powder is prepared by slurry polymerization. The rigid framework bridges the lumbar-fluorene metal compound as the main catalyst to control the molecular weight distribution and particle size, and form a viscosity-average molecular weight of 400,000 to 5 million g/mol and molecular weight. Polyethylene powder with a distribution index of 1.5 to 4.0 and an average particle size of ≤105μm improves its swelling and processing properties.
It significantly shortens the swelling time of polyethylene powder in solvent, improves processing performance and production efficiency, reduces costs, and optimizes mechanical properties, and is suitable for lithium battery separators and other fields.
Smart Images

Figure CN119119340A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymers, and in particular to an olefin polymer and a preparation method thereof. Background Art
[0002] High molecular weight polyethylene powder is widely used in the fields of films, sheets, microporous membranes, fibers, foams, tubes, battery separators, etc. due to its excellent tensile processability, high strength and high chemical stability. Among them, high molecular weight polyethylene powder generally has high viscosity and is difficult to process by injection molding, so most of them are added to solvents for forming. For example, CN108752607B screens specific high molecular weight polyethylene powders for preparing microporous membranes and high-strength fibers, but the high molecular weight polyethylene powder is produced by continuous processing with aluminum hydroxide containing a specific number and a specific size. Its yield is excellent and the product size stability is excellent. The preparation method of the powder in this method is complicated and costly.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] In the experiment, it was found that the swelling properties of high molecular weight polyethylene powder in solvents affect the production efficiency and density of the products prepared therefrom, and further affect the strength and processing properties of the products. Generally, when there are no branches in high molecular weight and ultra-high molecular weight polyethylene, it is beneficial to improve mechanical strength such as tensile strength and modulus, but its high melt viscosity makes processing difficult. In order to improve processing properties, a branched structure can be introduced.
[0005] The present invention has found that if the dual catalytic system in the invention patent CN113748141B is used to prepare high-density polyethylene with a molecular weight of about 400,000-600,000 g / mol and long chain branching, there are usually more short chain branches and a large number of long chain branches in the higher molecular weight part, and there are no large number of long chain branches in the extremely high molecular weight part. Although the processing performance can be improved, the application of the dual catalytic system not only increases the catalyst cost, but also causes a large number of short chain branches to reduce the mechanical properties.
[0006] Therefore, for high molecular weight polyethylene powder, it is necessary to solve the problem that the powder takes a long time to swell in the solvent during solution spinning, which is not conducive to improving production efficiency, and it is also necessary to avoid the defects caused by the branched structure.
[0007] The present invention provides an olefin polymer and a preparation method thereof, which are used to solve the defect that the processing performance of high-density polyethylene powder in the prior art is difficult to improve. A polymer powder with high viscosity-average molecular weight, narrow molecular weight distribution and high particle size uniformity is obtained by forming long branches in the molecular structure through a slurry polymerization process, and is used to realize the preparation of an ethylene polymer with good swelling and good fluidity, so that the polymer has better processing performance.
[0008] The present invention provides an ethylene polymer, which is a polyethylene powder prepared by a slurry polymerization process, containing long chain branches, having a viscosity average molecular weight of 400,000 to 5,000,000 g / mol, a molecular weight distribution index (PDI) of 1.5 to 4.0 and an average particle size of ≤105 μm.
[0009] Through experiments, it was found that the polyethylene powder of the above structure obtained by the present invention not only has a low molecular weight distribution index and a small average particle size (compared with the polyethylene powder prepared by the existing catalyst using the slurry polymerization process, which is mainly 110-130 μm), but also has a higher swelling degree and a shorter swelling time in the solvent, better processing performance during processing, and high production efficiency.
[0010] According to the ethylene polymer provided by the present invention, in order to further improve the swelling performance and processing performance of the polyethylene powder, it is preferred that the long chain branch is an alkane group of 50 to 200 carbon atoms, and the CY-a parameter at 190°C is less than 0.15; it is further preferred that the proportion of the long chain branch in the polyethylene powder is 1 to 6 long chain branches / 100,000 carbons; and it is further preferred that the bulk density of the polyethylene powder is 0.2 to 0.4 g / cm 3 , high particle size uniformity,
[0011] The present invention also provides a method for preparing the above-mentioned ethylene polymer, which is prepared by copolymerizing ethylene and a comonomer using a slurry polymerization process with a rigid skeleton bridged cyclopentadienyl-fluorene metal compound as a main catalyst;
[0012] The structural formula of the rigid skeleton bridged cyclopentadienyl-fluorene metal compound is shown in Formula I:
[0013]
[0014] Among them, linker is or
[0015] R1 is independently selected from an ether group containing at least one oxygen atom and 2 to 20 carbon atoms;
[0016] R2 is a C1 to C18 hydrocarbon group;
[0017] M is Zr or Hf;
[0018] Each X is independently selected from chlorine, bromine or iodine.
[0019] Compared with the prior art of improving the processing performance and product performance of high-density polyethylene by introducing substances such as aluminum hydroxide, the method of the present invention has the advantages of mature polymerization process, low cost, convenient molecular weight adjustment and simple post-processing.
[0020] The method for preparing the rigid skeleton bridged cyclopentadienyl-fluorene metal compound of the present invention comprises: firstly reacting compound a with organic lithium to prepare substituted fluorenyl lithium; then reacting a fulvene compound with the substituted fluorenyl lithium to obtain a mixed solution; then adding organic lithium to the mixed solution, and finally adding MX4 to react to generate the rigid skeleton bridged cyclopentadienyl-fluorene metal compound;
[0021] The structural formula of the compound a is: Wherein, R1 is independently selected from an ether group containing at least one oxygen atom and 2 to 20 carbon atoms;
[0022] The structural formula of the fulvene compound is:
[0023] or Wherein, R2 is a C1 to C18 hydrocarbon group;
[0024] Preferably, the organic lithium is one or more of n-butyl lithium, sec-butyl lithium, tert-butyl lithium, methyl lithium, and phenyl lithium, and the preferred alkyl lithium is n-butyl lithium;
[0025] Preferably, the MX4 is a zirconium or hafnium halide, more preferably zirconium tetrachloride or hafnium tetrachloride.
[0026] The preparation process of the compound a comprises: reacting 2,7-dihydroxyfluorene with a monohalogenated ether compound under the action of a base to obtain the compound; the base is one or more of sodium methoxide, sodium ethoxide, butyl lithium, methyl lithium, phenyl lithium, sodium hydroxide, potassium hydroxide, sodium carbonate, potassium carbonate or cesium carbonate, and the preferred base is one or more of lithium carbonate, sodium carbonate, potassium carbonate or cesium carbonate, preferably potassium carbonate; the monohalogenated ether compound is one or more of chloromethyl methyl ether, 1-chloromethyl ethyl ether, 1-chloromethyl propyl ether, 2-methoxyethoxymethyl chloride, 1-bromo-2-methoxyethane, 1-(2-chloroethoxy)-2-methoxyethane, 2-ethoxyethyl bromide, 2-(2-ethoxyethoxy)ethyl bromide, 1-bromo-3-methoxypropane, 1-bromo-3-ethoxypropane, 1-bromo-4-methoxybutane and 1-bromo-5-methoxypentane.
[0027] The preparation process of the fulvene compound comprises: reacting a monosubstituted cyclopentadiene with a ketone compound b under the action of a strong base to obtain the fulvene compound; the substituent on the monosubstituted cyclopentadiene is a C1 to C18 hydrocarbon group (the substituent becomes R2 in the rigid skeleton bridged cyclopentene-fluorene metal compound after the above reaction); the structural formula of the ketone compound b is:
[0028] or
[0029] The strong base is one or more of sodium methoxide, sodium ethoxide, butyl lithium, methyl lithium, phenyl lithium, sodium hydroxide, and potassium hydroxide; preferably, the strong base is sodium methoxide, sodium ethoxide, or butyl lithium.
[0030] When preparing the above-mentioned compound a, the preparation of fulvene compounds, and the preparation of metallocene-fluorene compounds from the two, any one or both of them can be carried out under an inert atmosphere selected from argon, helium, nitrogen, and a mixture of the above gases.
[0031] When preparing the above-mentioned compound a, the preparation of the fulvene compound, and the preparation of the metallocene-fluorene compound from the two, any one or both of them can be carried out under the condition of using an organic medium, and the organic medium is selected from one or more of pentane, hexane, cyclohexane, tetrahydrofuran, ether, benzene, toluene, xylene, chloroform, dichloromethane and petroleum ether.
[0032] According to the method for preparing an ethylene polymer provided by the present invention, the rigid skeleton bridged cyclopentadienyl-fluorene metal compound is:
[0033] or
[0034] The method for preparing an ethylene polymer provided by the present invention comprises:
[0035] Under a nitrogen atmosphere, the main catalyst, the co-catalyst, and the activator-carrier are mixed in a diluent to obtain a first product;
[0036] The comonomer is added to the first product, and ethylene gas is introduced to a certain pressure. After polymerization at 20-150° C. for a certain period of time, the introduction of ethylene gas is stopped, and the obtained product is dried at a temperature of 50-70° C. and under reduced pressure to obtain the ethylene polymer; the comonomer is one or more of 1-butene, 1-hexene and 1-octene.
[0037] The polymerization reaction temperature is preferably 60 to 100°C.
[0038] According to the method for preparing ethylene polymers provided by the present invention, the co-catalyst is an organic aluminum, preferably one or more of trimethyl aluminum, methylaluminoxane, triethyl aluminum, diethyl aluminum chloride and triisobutyl aluminum;
[0039] The diluent is one or more of isobutane, normal butane, normal pentane, isopentane, neopentane, cyclopentane, normal hexane, cyclohexane, normal heptane, benzene, toluene and xylene;
[0040] The activator-support is one or more of fluorinated alumina, fluorinated silica-alumina, fluorinated silica-coated alumina, sulfated alumina, sulfated silica, sulfated silica-alumina and sulfated silica-coated alumina.
[0041] According to the preparation method of the ethylene polymer provided by the present invention, hydrogen is introduced simultaneously with the introduction of ethylene gas to adjust the viscosity-average molecular weight of the ethylene polymer; preferably, hydrogen of ≤0.08MPa is introduced simultaneously with the introduction of ethylene gas.
[0042] According to the method for preparing ethylene polymer provided by the present invention, the amount of the diluent added is determined based on the volume of the reactor and does not exceed 70% of the volume of the reactor.
[0043] According to the method for preparing ethylene polymer provided by the present invention, the contents of the main catalyst, the co-catalyst and the activator-carrier in the reaction system are 0.2-3.0 ppm, 25-500 ppm and 50-1000 ppm respectively.
[0044] The present invention also provides use of the above-mentioned ethylene polymer in a lithium battery separator.
[0045] The present invention provides an olefin polymer and a preparation method thereof. A polyethylene powder having a viscosity-average molecular weight of 400,000 to 5,000,000 g / mol, a molecular weight distribution index of 1.5 to 4.0 and an average particle size of ≤105 μm is prepared by a slurry polymerization process. The powder has good swelling properties, contains long chain branches, and has good processing properties, and is particularly suitable for the field of lithium battery separators. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 It is the molecular weight distribution diagram of the olefin polymer in Examples 1 to 4 provided by the present invention. DETAILED DESCRIPTION
[0048] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0049] Combine the following Figure 1 An olefin polymer and a method for preparing the same are described.
[0050] If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased through regular channels. Among them, the main raw materials are prepared as follows:
[0051] Main catalyst: Directly weigh the powdered solid and add it under an inert atmosphere.
[0052] Co-catalyst solution: trimethylaluminum hexane solution, concentration 1.0 mol / L, purchased from J&K Technology Co., Ltd.; triethylaluminum hexane solution, concentration 1.0 mol / L, purchased from J&K Technology Co., Ltd.; triisobutylaluminum hexane solution, concentration 1.0 mol / L, purchased from J&K Technology Co., Ltd.;
[0053] Activator-carrier: fluorinated alumina, fluorinated silica. Alumina specifications: average particle size 100μm, specific surface area 400m 3 / g, pore volume 1.5ml / g. The preparation method of fluorinated alumina is as follows: 2g of ammonium bifluoride is dissolved in 2ml of methanol, then mixed evenly with 18g of alumina, vacuum dried to remove the solvent methanol, calcined in a muffle furnace at 600℃ for 4h under nitrogen flow, and stored in anhydrous and oxygen-free state for later use. The preparation method of fluorinated silicon dioxide is similar to that of fluorinated alumina.
[0054] Comonomers: 1-hexene, 1-octene. Molecular sieve and alumina are used for drying to remove water and oxygen, and vacuum distillation is performed, and the mixture is stored under anhydrous and oxygen-free conditions for future use.
[0055] Further, the preparation of the main catalyst is as follows:
[0056] Preparation Example 1
[0057] Preparation of compound a: Add 2,7-dihydroxyfluorene (19.8 g, 100 mmol) to a 500 ml round-bottom flask, add 200 ml tetrahydrofuran as a solvent, add potassium carbonate (30.36 g, 220 mmol) and react for 30 min, add 2-bromoethyl methyl ether (29.2 g, 105 mmol) dropwise and react at room temperature for 6 h, filter to remove excess potassium carbonate, remove the solvent tetrahydrofuran and excess 2-bromoethyl methyl ether in vacuo to obtain a white solid, wash with 20 ml cold methanol and dry in vacuo to obtain 29.1 g of white 2,7-di(methoxyethoxy)fluorene, with a yield of 92.6%. The structural formula of the 2,7-di(methoxyethoxy)fluorene is as follows:
[0058]
[0059] The 1HNMR (300 MHz, CDCl3) δ of the 2,7-di(methoxyethoxy)fluorene is: 7.96-7.98 (d, J = 7.8 Hz, 2H), 7.17-7.18 (d, J = 7.9 Hz, 2H), 7.0 (m, 2H), 3.87 (m, 2H), 3.77-3.79 (t, J = 7.3 Hz, 4H), 4.31-4.33 (t, J = 7.6, 1.3 Hz, 4H), 3.41 (m, 6H).
[0060] Preparation of fulvene compounds: Add fluorenone (90.1g, 500mmol), sodium methoxide (32.4g, 600mmol) and methanol (450mL) to a 1000ml round-bottom flask. Add butylcyclopentadiene (120g, 1000mmol) dropwise, and stir the mixture to obtain an orange precipitate. After stirring the reaction for 10h, filter the orange precipitate, wash it with 50mL of cold methanol and vacuum dry it for 8 hours to obtain 96.6g of fulvene, with a yield of 68.5%. The structural formula of the fulvene compound is as follows:
[0061]
[0062] The 1HNMR (300 MHz, CDCl3) δ of the fulvene compound is: 7.94-7.95 (d, J = 7.4 Hz, 2H), 7.57-7.58 (d, J = 7.3 Hz, 2H), 7.47-7.49 (t, J = 7.2 Hz, 2H), 7.37-7.39 (t, J = 7.4, 2H), 6.6-6.63 (dd, J = 5.1 Hz, 1.4 Hz, 1H), 6.40-6.42, (dd, J = 5.1 Hz, 1.4 Hz, 1H), 6.12 (m, 1H), 5.82-5.98 (m, 1H), 4.94-5.16 (m, 2H), 2.55-2.60 (t, J = 7.2 Hz, 2H), 2.33 (t, J = 7.2 Hz, 2H).
[0063] Under nitrogen atmosphere, add the prepared 2,7-di(methoxyethoxy)fluorene (3.14 g, 10 mmol) into a 100 ml round-bottom flask, add 30 ml of anhydrous tetrahydrofuran and cool to 0°C, gradually add dropwise 2.4 M n-butyllithium hexane solution (4.2 ml, 10.1 mmol), gradually increase the temperature to room temperature and react for 3 h to prepare substituted fluorenyl lithium.
[0064] Under nitrogen atmosphere, the fulvene compound (2.82 g, 10 mmol) prepared above was dissolved in 20 ml tetrahydrofuran, and added to the substituted fluorenyl lithium solution to react for 4 h to obtain a mixed solution, which can be directly used for the next step of synthesis, that is, 2.4 M n-butyl lithium hexane solution (4.2 ml, 10.1 mmol) was added to the mixed solution at 0 ° C, reacted at room temperature for 4 h, and then zirconium tetrachloride (2.33 g, 10 mmol) was added to react at room temperature for 12 h, filtered and the filter cake was washed with 10 ml n-hexane. The filter cake was dissolved in 10 ml dichloromethane, and 10 ml n-hexane was slowly added as a poor solvent for recrystallization, and placed in a refrigerator. After 24 h, a large amount of crystals precipitated, filtered and the filter cake was washed with 3×5 ml n-hexane, and the filter cake was vacuum dried to obtain 3.54 g of compound Zr1, with a yield of 45.0%.
[0065] The structural formula of the compound Zr1 is as follows:
[0066]
[0067] The 1HNMR (300 MHz, CDCl3) δ of the compound is: 8.08 (d, J = 8.0 Hz, 1H), 7.90 (d, J = 7.4 Hz, 4H), 7.68 (m, 2H), 7.54 (d, J = 7.3 Hz, 2H), 7.46 (t, J = 7.2 Hz, 2H), 7.36 (t, J = 7.4, 2H), 7.10-7.2 (d, 2H), 6.28 (m,1H),6.28(m,1H),5.82-5.9(t,J=2.7Hz,1H),4.2-4.26(t,J=7.8,1.3Hz,4H),3.92-3. 97(t,J=7.2Hz,4H),3.51(m,6H),2.54-2.68(t,J=7.2Hz,2H),2.31-2.36(t,J=7.6Hz,2H).
[0068] Preparation Example 2
[0069] A rigid skeleton bridged cyclopentadienyl-fluorene metal compound, the structural formula of which is:
[0070]
[0071] The preparation method of the above-mentioned compound is basically the same as that of Preparation Example 1, except that the fluorenone in the preparation of the fulvene compound is replaced by xanthone; wherein the yield of the obtained fulvene compound is 72.1%, and the yield of the synthesis of the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Zr2 is 48.5%.
[0072] Preparation Example 3
[0073] A rigid skeleton bridged cyclopentadienyl-fluorene metal compound, the structural formula of which is:
[0074]
[0075] The preparation method of the above-mentioned compound is basically the same as that of Preparation Example 1, except that the anthracene ketone in the preparation of the fulvene compound is replaced by 10,10-dimethylanthracenone; wherein the yield in the preparation of the fulvene compound is 64.7%, and the yield in the synthesis of the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Zr3 is 43.3%.
[0076] Preparation Example 4
[0077] A rigid skeleton bridged cyclopentadienyl-fluorene metal compound, the structural formula of which is:
[0078]
[0079] The preparation method of the above compound is basically the same as that of Preparation Example 1, except that zirconium tetrachloride is replaced by hafnium tetrachloride; wherein the yield of the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Hf1 is 54.3%.
[0080] Example 1
[0081] A method for preparing an olefin polymer, the specific polymerization steps are as follows:
[0082] (1) Place the reactor in an oil bath at 95°C and evacuate for 3 h, then replace with nitrogen three times while maintaining a slight positive pressure, and cool to 95°C;
[0083] (2) In a 5L reactor, 2 mg of the main catalyst Zr1 (prepared in Preparation Example 1), 2 ml of a 1 mol / L hexane solution of the co-catalyst triethylaluminum and 200 mg of activator-carrier fluorinated alumina were placed separately under a nitrogen atmosphere and aged for 5 minutes. In a nitrogen atmosphere, 2000 g of the reaction solvent, i.e., the diluent isobutane, were added.
[0084] (3) 20 g of the comonomer hexene was added, and then ethylene was immediately introduced until the pressure in the reactor reached 4.5 MPa to start polymerization.
[0085] (4) After 2 hours of polymerization, turn off the ethylene immediately, stop stirring, cool to 60°C and maintain this temperature, and remove the solvent under reduced pressure to obtain polyethylene.
[0086] Example 2
[0087] A method for preparing an olefin polymer is basically the same as that of Example 1, except that the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Zr1 in Example 1 is replaced by the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Zr2 obtained in Preparation Example 2.
[0088] Example 3
[0089] A method for preparing an olefin polymer is basically the same as that of Example 1, except that the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Zr1 in Example 1 is replaced by the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Zr3 obtained in Preparation Example 3.
[0090] Example 4
[0091] A method for preparing an olefin polymer is basically the same as that of Example 1, except that the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Zr1 in Example 1 is replaced by the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Hf1 obtained in Preparation Example 4.
[0092] Example 5
[0093] A method for preparing an olefin polymer is basically the same as that of Example 1, except that the polymerization temperature of 95°C in Example 1 is replaced by 120°C.
[0094] Example 6
[0095] A method for preparing an olefin polymer is substantially the same as that of Example 1, except that the co-catalyst triethylaluminum is replaced by a hexane solution of triisobutylaluminum.
[0096] Example 7
[0097] A method for preparing an olefin polymer is substantially the same as that of Example 1, except that the activator-carrier fluorinated alumina in Example 1 is replaced by fluorinated silica.
[0098] Example 8
[0099] A method for preparing an olefin polymer is substantially the same as that of Example 1, except that the comonomer 1-hexene in Example 1 is replaced by 1-octene.
[0100] Example 9
[0101] A method for preparing an olefin polymer is basically the same as that of Example 1, except that 0.05 MPa hydrogen is also introduced while introducing ethylene gas.
[0102] Comparative Example 1
[0103] A method for preparing an olefin polymer is substantially the same as that in Example 1, except that the rigid skeleton bridged cyclopentadienyl-fluorene metal compound in Example 1 is replaced by a bridged cyclopentadienyl-fluorene metal compound having the following structure:
[0104]
[0105] The preparation method of the above-mentioned rigid skeleton bridged cyclopentadienyl-fluorene metal compound is basically the same as that in Example 1, except that the fluorenone in the preparation of the fulvene compound is replaced by benzophenone; wherein the yield when preparing the fulvene compound is 75.2%, while the yield when preparing the above-mentioned catalyst is 46.9%.
[0106] Comparative Example 2
[0107] A method for preparing an olefin polymer is substantially the same as that in Example 1, except that the rigid skeleton bridged cyclopentadienyl-fluorene metal compound in Example 1 is replaced by a bridged cyclopentadienyl-fluorene metal compound having the following structure:
[0108]
[0109] The preparation method of the above catalyst is basically the same as that of Preparation Example 1, except that iodomethane is used instead of 2-bromoethyl methyl ether in the preparation of the substituted fluorene compound. The yield of the obtained compound 2,7-dimethoxyfluorene is 94.5%, while the yield of the above catalyst is 51.6%.
[0110] Comparative Example 3
[0111] Commercially available lithium battery separator material - polyethylene.
[0112] Molecular weight was determined by high temperature gel permeation chromatography.
[0113] The viscosity average molecular weight is measured by the intrinsic viscosity method.
[0114] The average particle size was measured by Mastersizer 2000.
[0115] Swelling test
[0116] The specific operation is as follows: weigh 2 grams of polymer sample, add it to the sealed cylindrical sample pool of the rheometer, then add 10 mL of white oil, heat it to 122 ° C at a rate of 10 ° C / min, keep it constant, and count the time as 0, then record the change of solution viscosity over time. When the solution viscosity begins to increase rapidly, it is considered that the polymer has completely swelled and started to partially disentangle, and the time is recorded as t1. Stop the rheometer immediately, lift the rotating arm, remove the cylinder and pour out the solvent that can flow out to record the volume V mL, then the swelling degree is (10-V) / 2.
[0117] The polymers obtained in Examples 1 to 9 and Comparative Examples 1 and 3 were tested, and the test results are as follows:
[0118]
[0119]
[0120] The molecular weight distribution diagrams of the polymers obtained in Example 1 (PE 1), Example 2 (PE 2), Comparative Example 1 (PE 01) and Comparative Example 2 (PE 02) are as follows: Figure 1 As shown, combined with the data in the above table, it can be seen that the molecular weight of the polymer in Example 1 is significantly higher than that in the comparative example, and the molecular weight distribution is narrower. This is because the bridge of the rigid skeleton makes the metal active center more compact, which is beneficial to the increase of the molecular weight, and the long-chain methoxyethoxy group is beneficial to the stability of the active center, weakening the chain transfer reaction and the bimolecular deactivation reaction.
[0121] Compared with Example 1 and Example 2 and 3, the rigid skeleton bridged cyclopentadienyl-fluorene metal compounds prepared by xanthone and 10,10-dimethylanthracenone have greater steric hindrance than the metal center in Zr1, and the electronic effect is also different, resulting in the preparation of polyethylene with higher molecular weight in Example 2 and 3, with a viscosity average molecular weight of up to 4.67×10 6 g / mol, which already belongs to the category of ultra-high molecular weight polyethylene.
[0122] Compared with Example 1 and Example 5, the molecular weight of the polymer decreased when the polymerization was carried out at a higher temperature, indicating that the increase in temperature is conducive to the chain transfer reaction.
[0123] Compared with Example 1 and Example 6, after the co-catalyst was replaced by triethylaluminum with a hexane solution of triisobutylaluminum, the molecular weight of the obtained polyethylene increased, the molecular weight distribution became narrower, and the number of long chain branches was significantly reduced, resulting in a prolonged swelling time.
[0124] Compared with Example 1 and Example 7, after the catalyst carrier was replaced by fluorinated alumina with fluorinated silica, the polymer molecular weight and molecular weight distribution were basically similar, but the average particle size of the polymer changed from 97 to 103 μm, resulting in a 26% extension of the swelling time.
[0125] Compared with Example 1 and Example 8, the comonomer is replaced by 1-octene from 1-hexene. Although the molecular weight of the obtained polyethylene is slightly increased, the swelling time is shorter, which may be caused by the longer length of the long chain branches and the greater number of long chain branches.
[0126] Compared with Example 1 and Example 9, the viscosity average molecular weight of polyethylene increased from 3.72×10 6 g / mol decreased to 1.78×10 6 g / mol, which already meets the molecular weight requirements of lithium battery separator materials (0.4×10 6 g / mol~2.0×10 6 This also shows that the catalytic system is sensitive to hydrogen and the polymer molecular weight can be adjusted by adjusting the amount of hydrogen added.
[0127] Compared with Example 9 and Comparative Example 3, the average particle size of polyethylene in Example 9 is 96 μm, which is significantly smaller than the particle size of commercial lithium battery separator material 108 μm, and the swelling time of 15 min is also significantly shorter than the swelling time of commercial lithium battery separator material 24 min, which is beneficial to shorten the actual industrial processing time and improve production efficiency.
[0128] Compared with Example 1, the rigid skeleton bridged cyclopentadienyl-fluorene metal compound Zr1 in Example 1 was replaced with the same rigid skeleton bridged cyclopentadienyl-fluorene metal compound Hf1. The molecular weight of the obtained polymer was significantly reduced, the average particle size was also smaller, the swelling time was 11min shorter, and the viscosity average molecular weight was 1.52×10 6 g / mol, and can also be used as a diaphragm material. Moreover, compared with Comparative Example 3, the diaphragm material introduces a long branched chain structure, the swelling time is greatly shortened, the processing performance is better, and it is helpful to improve the production efficiency.
[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. An ethylene polymer, characterized in that The polyethylene powder is prepared by slurry polymerization process and contains long chain branches, a viscosity average molecular weight of 400,000 to 5,000,000 g / mol, a molecular weight distribution index of 1.5 to 4.0, and an average particle size of ≤105 μm.
2. The ethylene polymer according to claim 1, characterized in that The long chain branch is an alkane group with 50 to 200 carbon atoms, and the CY-a parameter at 190° C. is less than 0.
15.
3. The ethylene polymer according to claim 2, characterized in that The long chain branches account for 1 to 6 long chain branches per 100,000 carbon atoms in the polyethylene powder.
4. The method for preparing an ethylene polymer according to any one of claims 1 to 3, characterized in that: The method uses a rigid skeleton bridged cyclopentadiene-fluorene metal compound as the main catalyst and adopts a slurry polymerization process to copolymerize ethylene and a comonomer to obtain the product; The structural formula of the rigid skeleton bridged cyclopentadienyl-fluorene metal compound is shown in Formula I: Among them, linker is or R1 is independently selected from an ether group containing at least one oxygen atom and 2 to 20 carbon atoms; R2 is a C1 to C18 hydrocarbon group; M is Zr or Hf; Each X is independently selected from chlorine, bromine or iodine.
5. The method for preparing an ethylene polymer according to claim 4, wherein: The rigid skeleton bridged cyclopentadienyl-fluorene metal compound is: or 6. The method for preparing an ethylene polymer according to claim 4 or 5, characterized in that: include: Under a nitrogen atmosphere, the main catalyst, the co-catalyst, and the activator-carrier are mixed in a diluent to obtain a first product; The comonomer is added to the first product, and ethylene gas is introduced to a certain pressure. After polymerization at 20-150° C. for a certain period of time, the introduction of ethylene gas is stopped, and the obtained product is dried at a temperature of 50-70° C. and under reduced pressure to obtain the ethylene polymer.
7. The method for preparing an ethylene polymer according to claim 6, wherein: The comonomer is one or more of 1-butene, 1-hexene and 1-octene.
8. The method for preparing an ethylene polymer according to claim 6, wherein: The co-catalyst is an organic aluminum, preferably one or more of trimethyl aluminum, methylaluminoxane, triethyl aluminum, diethyl aluminum chloride and triisobutyl aluminum; more preferably triisobutyl aluminum; The diluent is one or more of isobutane, normal butane, normal pentane, isopentane, neopentane, cyclopentane, normal hexane, cyclohexane, normal heptane, benzene, toluene and xylene; The activator-support is one or more of fluorinated alumina, fluorinated silica-alumina, fluorinated silica-coated alumina, sulfated alumina, sulfated silica, sulfated silica-alumina and sulfated silica-coated alumina.
9. The method for preparing an ethylene polymer according to any one of claims 6 to 8, characterized in that: The introduction of hydrogen gas simultaneously with the introduction of ethylene gas is used to regulate the viscosity average molecular weight of the ethylene polymer; preferably, the introduction of hydrogen gas at ≤0.08 MPa simultaneously with the introduction of ethylene gas.
10. The method for preparing an ethylene polymer according to any one of claims 6 to 8, characterized in that: The amount of the diluent added does not exceed 70% of the volume of the reactor.
11. The method for preparing an ethylene polymer according to claims 6 to 10, characterized in that: The contents of the main catalyst, the co-catalyst and the activator-carrier in the reaction system are 0.2-3.0 ppm, 25-500 ppm and 50-1000 ppm respectively.
12. Use of the ethylene polymer according to any one of claims 1 to 3 in a lithium battery separator, characterized in that: The viscosity average molecular weight of the ethylene polymer is 0.4×10 6 g / mol~2.0×10 6 g / mol.
Citation Information
Patent Citations
High molecular weight polyethylene powder, microporous membranes, and high-strength fibers
CN108752607B
A dual-catalyst system for producing high-density polyethylene with long-chain branching.
CN113748141B
